Peptide-based electrochemical biosensors utilized for protein detection - Váňová, Veronika; Mitrevska, Katerina; Milosavljevic, Vedran; Hynek, David; Richtera, Lukas; Adam, Vojtech (Biosensors & bioelectronics, 2021)
Proteins are generally detected as biomarkers for tracing or determining various disorders in organisms. Biomarker proteins can be tracked in samples with various origins and in different concentrations, revealing whether an organism is in a healthy or unhealthy state. In regard to detection, electrochemical biosensors are a potential fusion of electronics, chemistry, and biology, allowing for fast and early point-of-care detection from a biological sample with the advantages of high sensitivity, simple construction, and easy operation. Peptides present a promising approach as a biorecognition element when connected with electrochemical biosensors. The benefits of short peptides lie mainly in their good stability and selective affinity to a target analyte. Therefore, peptide-based electrochemical biosensors (PBEBs) represent an alternative approach for the detection of different protein biomarkers. This review provides a summary of the past decade of recently proposed PBEBs designed for protein detection, dividing them according to different protein types: (i) enzyme detection, including proteases and kinases; (ii) antibody detection; and (iii) other protein detection. According to these protein types, different sensing mechanisms are discussed, such as the peptide cleavage by a proteases, phosphorylation by kinases, presence of antibodies, and exploiting of affinities; furthermore, measurements are obtained by different electrochemical methods. A discussion and comparison of various constructions, modifications, immobilization strategies and different sensing techniques in terms of high sensitivity, selectivity, repeatability, and potential for practical application are presented.
Keywords: protilátky; Electrochemical Techniques; biologické markery; Peptides; biosenzitivní techniky; peptidy; Biomarkers; elektrochemické techniky; Antibodies; Biosensing Techniques